2020
DOI: 10.1038/s41598-020-67887-6
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus modality influences session-to-session transfer of training effects in auditory and tactile streaming-based P300 brain–computer interfaces

Abstract: Despite recent successes, patients suffering from locked-in syndrome (LIS) still struggle to communicate using vision-independent brain–computer interfaces (BCIs). In this study, we compared auditory and tactile BCIs, regarding training effects and cross-stimulus-modality transfer effects, when switching between stimulus modalities. We utilized a streaming-based P300 BCI, which was developed as a low workload approach to prevent potential BCI-inefficiency. We randomly assigned 20 healthy participants to two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The UCD evaluation process is built around metrics to determine effectiveness (accuracy in percent of correct responses), efficiency (information transfer rate in bits/min and subjective workload) and satisfaction (via visual analog scale, questionnaire, or user interview) [137,138]. These metrics should also inform earlier stage BCI development before end-user evaluation [139,140]. Further factors should be considered when designing the BCI paradigm, for instance, the design of tasks, feedback, instructions, and signal processing [86,[141][142][143].…”
Section: Organizer: Sebastian Halder (University Of Essex)mentioning
confidence: 99%
“…The UCD evaluation process is built around metrics to determine effectiveness (accuracy in percent of correct responses), efficiency (information transfer rate in bits/min and subjective workload) and satisfaction (via visual analog scale, questionnaire, or user interview) [137,138]. These metrics should also inform earlier stage BCI development before end-user evaluation [139,140]. Further factors should be considered when designing the BCI paradigm, for instance, the design of tasks, feedback, instructions, and signal processing [86,[141][142][143].…”
Section: Organizer: Sebastian Halder (University Of Essex)mentioning
confidence: 99%
“…While a multi-session training is usually not necessary for visual P300 paradigms, similar training-induced improvements have previously been observed in BCIs based on auditory stimulation 19 , 25 . It has even been demonstrated that BCI competence acquired from training with an auditory paradigm can, to a degree, be transferred to the tactile modality 32 .…”
Section: Introductionmentioning
confidence: 99%
“…It was also meant by this method that there may be a need for several devices and a suitable place at the same time to study or work ( Cowden and Young, 2020 ; Filandri and Semi, 2020 ; Lucisano et al, 2020 ; Ranieri et al, 2020 ; Mohsin et al, 2021a ; Naseem et al, 2021 ). Several teachers considered it as a source of stress to overcome these challenges in managing the distant learning process ( Cowden and Young, 2020 ; Palareti et al, 2020 ; Ziebell et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%